The Effect of Competency and Compensation on Employee Performance at PT Setia Sejahtera Perkasa - Ramdhan, Muhammad; Ridwan, Muhamad (Universitas Syiah Kuala, 2023)
This study aims to determine the effect of competence and compensation on employee performance at PT Setia Sejahtera Perkasa. This type of research is causality research, compiled to examine the possibility of causal relationships between variables. The sampling technique uses a saturated sample of 49 respondents. The results showed that competence and compensation positively and significantly affected employee performance with an influence contribution of 57.9%. In comparison, the remaining 42.1% was influenced by other factors that were not studied in this study. The results of the hypothesis test show a Fcalculated value of 31.607 greater than the Ftable of 3.20 with a significant level of 0.000 smaller than 0.05. So, it can be concluded that together, competence and compensation have a positive and significant effect on employee performance at PT Setia Sejahtera Perkasa.